49.9k views
1 vote
What is equation is equivalent to 6(3p-2)=20?

User Gabe H
by
6.6k points

2 Answers

6 votes

Answer:


p = (16)/(9) \\

Explanation:


6(3p - 2) = 20 \\ 18p - 12 = 20 \\ 18p = 32 \\ (18p)/(18) = (32)/(18) \\ p = (16)/(9)

User Celius Stingher
by
5.8k points
4 votes

Answer:


p=(16)/(9)

Explanation:


6(3p-2)=20

Distribute the brackets.


6(3p)+6(-2)=20


18p-12=20

Add
12 on both sides.


18p-12+12=20+12


18p=20+12


18p=32

Divide
18 on both sides.


(18p)/(18)=(32)/(18)


p=(16)/(9)

User Renukaradhya
by
7.1k points